2011
DOI: 10.1021/bm201079n
|View full text |Cite
|
Sign up to set email alerts
|

Pore Size Determination of TEMPO-Oxidized Cellulose Nanofibril Films by Positron Annihilation Lifetime Spectroscopy

Abstract: Wood cellulose nanofibril films with sodium carboxylate groups prepared from a 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized pulp exhibited an extremely low oxygen permeability of 0.0008 mL μm m(-2) day(-1) kPa(-1) at 0% relative humidity (RH). Positron annihilation lifetime spectroscopy (PALS) was used to determine the pore sizes in wood and tunicate TEMPO-oxidized cellulose nanofibril (TOCN-COONa) films in a vacuum (i.e., at 0% RH). PALS analysis revealed that the pore size of the wood TOCN-COONa fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 67 publications
3
88
1
Order By: Relevance
“…In contrast, coating of the TOCN-COOH/ C 12 -amine salt did not improve the oxygen barrier property of the PET film at all. Because the film density of the TOCN-COOH/C 12 -amine salt was as low as 1.33 (Table 1), it is likely that pore sizes in the film are larger and thus oxygen molecules easily permeate through the film, whereas the TOCNCOONa film has a denser structure with much smaller pore sizes (Fukuzumi et al 2011). Thus, the introduction of abundant long-alkyl chains to TOCN by the formation of amine salts has a negative impact on oxygen barrier properties of the TOCN films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, coating of the TOCN-COOH/ C 12 -amine salt did not improve the oxygen barrier property of the PET film at all. Because the film density of the TOCN-COOH/C 12 -amine salt was as low as 1.33 (Table 1), it is likely that pore sizes in the film are larger and thus oxygen molecules easily permeate through the film, whereas the TOCNCOONa film has a denser structure with much smaller pore sizes (Fukuzumi et al 2011). Thus, the introduction of abundant long-alkyl chains to TOCN by the formation of amine salts has a negative impact on oxygen barrier properties of the TOCN films.…”
Section: Resultsmentioning
confidence: 99%
“…The TEMPO-oxidized cellulose thus prepared had a sodium carboxylate content of 1.72 mmol g -1 , which was determined by the conductivity titration method (Saito and Isogai 2004). A 0.15% dispersion of TOCN-COONa was prepared from the TEMPOoxidized cellulose by mechanical disintegration in water, details of which are described elsewhere (Saito et al 2006(Saito et al , 2007Fujisawa et al 2011a, b;Fukuzumi et al 2011). The TOCN with free carboxyl groups (TOCN-COOH) was nano-dispersed in a water-IPA mixture (1:1 by vol.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TOCNs prepared from native celluloses by TEMPO-mediated oxidation have high tensile strengths and Young's moduli of 3 GPa and 140 GPa, respectively 21), 22) , remarkable and efficient improvements in mechanical and other properties have been achieved for various TOCN/polymer, nanoclay/TOCN, carbon nanotube/TOCN, TOCN/glass fiber and nanometal particle/TOCN composites 23) 33) . Moreover, self-standing TOCN films, which are prepared by casting the TOCN/water dispersions and drying, have high oxygen barrier properties and low thermal expansion coefficients, owing to unique self-assembly nature of surface-anionic TOCN elements in water 34), 35) . In this review paper, some of our results recently reported are summarized and introduced.…”
Section: )14) 17)mentioning
confidence: 99%
“…These nematic-ordered structures in turn cause high-gas barrier properties of selfstanding TOCN films by closest packing between the TOCN elements in the dried films 34) , which have very Taken with and without cross polarizers. small average pore sizes ( 0.47 nm) determined by positron-annihilation lifetime spectroscopy 35) . When a dilute acid is added to the aqueous TOCNs _ COONa dispersions, the fluid TOCN dispersions turn to highly stiff TOCN _ COOH hydrogels even at low TOCN contents such as 0.1 % (i.e., 99.9 % water).…”
Section: Tocn Aerogels With High Transparencies and Heat Insulating Pmentioning
confidence: 99%